Economic efficiency of companies of hotel and restaurant business in kharkov region - Sheianova, Elina Dmytrivna (НТУ "ХПІ", 2018)
The article is devoted to the analysis of economic efficiency at the enterprises of the hotel and restaurant business. The article analyzes and generalises theoretical approaches to the definition of the essence of the efficiency of enterprises. Economic efficiency - achievement of the greatest results at the least labor costs. Economic efficiency is a concrete form of manifestation of the law of time saving, their connection is through the growth of labor productivity, its increase means the increase of the effectiveness of cumulative labor, the increase of the efficiency of all production, conditioned primarily by the progress of productive forces. The article considered the features of the hotel and restaurant industry in Ukraine as a kind economic research. The article explored the essence of the concepts of "organizational structure o f the hotel", "hotel management", "economic efficiency" and "criterion of economic efficiency". The main approaches to assessing the economic efficiency of the hotel and restaurant business are described. The proposed directions of improving the quality of service evaluation in hotels in the Kharkiv region. The main ways of improving the strategy and tactics of price management at enterprises of the sphere of services of hospitality and restaurant business in the Kharkiv region are proposed. The article examined the formation of a modern domestic tourism market, the deepening of specialization and cooperation in the work of tourist enterprises, provision of conditions for the development of various types of domestic and in ward tourism, integration of Ukraine into the system of the world tourism market, development of international cooperation in the field of tourism, as well as solutions of the whole a complex of tasks in the field of personnel in the hotel and restaurant industry. The problems of the hotel business market are considered. The main approaches to assessing the economic efficiency of enterprises' activities are described; The relationship between resources and production results has been investigated. Considered the place of hotel and restaurant services in the tourism industry and enterprises of hotel industry as an important component of the tourism industry.

Стаття присвячена аналізу економічної ефективності на підприємствах готельно-ресторанної справи. У статті досліджено та узагальнено теоретичні підходи до визначення сутності ефективності діяльності підприємств. Економічна ефективність - досягнення найбільших результатів за найменших витрат праці. Економічна ефективність - конкретна форма вияву закону економії часу, їх зв'язок здійснюється через зростання продуктивності праці її підвищення означає зростання ефективності сукупної праці, збільшення ефективності всього виробництва, зумовленої насамперед прогресом продуктивних сил. У статті було розглянуто особливості готельно-ресторанної галузі в Україні як вид економічної дослідження. У статті було досліджено сутність понять "організаційна структура готелю", "менеджмент готельного господарства", "економічна ефективність" і "критерій економічної ефективності". Надано характеристику основних під ходів до оцінювання економічної ефективності діяльності підприємств готельно-ресторанної справи. Запропоновані напрями вдосконалення оцінки якості обслуговування в готелях в Харківському регіоні. Запропоновані основні шляхи вдосконалення стратегії і тактики управління цінами на підприємствах сфери послуг гостинності та ресторанної справи в Харківському регіоні. У статті було досліджено формування сучасного вітчизняного туристського ринку, поглиблення спеціалізації і кооперації в роботі туристських підприємств, забезпечення умов для розвитку різних видів внутрішнього і в'їзного туризму, інтеграція України до системи світового туристичного ринку, розвиток міжнародного співробітництва в сфері туризм, а також вирішення цілого комплексу завдань в сфері кадрів в готельно-ресторанної галузі. Розглянуті проблеми ринку готельної справи. Надано характеристику основних підходів до оцінювання економічної ефективності діяльності підприємств; досліджено зв'язок між ресурсами і результатами виробництва. Розглянуто місце готельно-ресторанних послуг в індустрії туризму та підприємства готельного господарства, як важлива складова індустрії туризму.
Економічна ефективність підприємств готельно-ресторанної справи в харківському регіоні
Keywords: effectiveness; rational use; management; діяльність підприємства; раціональне використання; результативність; економічні відносини